OPTIMALISASI KEMAMPUAN MENULIS AKSARA BALI MELALUI MODEL GAME-BASED LEARNING PADA SISWA KELAS VII SMP - Diantari, Ni Putu; Ludy Paryatna, Ida Bagus Made; Rai, Ida Bagus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aimed to improve students’ learning outcomes and motivation in learning Balinese script through the application of the Game-Based Learning (GBL) model. This study employed a classroom action research design conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of the study were seventh-grade students in class VIIA during the academic year. Data were obtained through learning outcome tests and motivation questionnaires, and were analyzed using descriptive quantitative techniques. The results showed that the implementation of the GBL model improved students’ learning outcomes, as indicated by an increase in the average score from 71.09 in cycle I to 80.56 in cycle II, as well as an improvement in learning completeness from 65.62% to 96.87%. Students’ motivation and participation in learning also increased, as reflected in their higher engagement and enthusiasm during the learning process. Therefore, the implementation of the GBL model proved effective in creating a more interactive learning environment and enhancing students’ learning outcomes.